The Effectiveness of Digital Storytelling in Improving Self-Efficacy of Chronic Kidney Failure Patients Undergoing Hemodialysis - Andi Sulfikar; Abdul Thalib; Indah Restika BN (GLOBAL HEALTH SCIENCE GROUP, 2024)
Chronic Kidney Disease (CKD) is a widespread health concern that greatly affects the physical and mental well-being of individuals, particularly those who undergo hemodialysis (HD). Managing this condition poses significant challenges for patients, often leading to reduced self-efficacy. Digital storytelling has been identified as a potentially effective method for improving self-efficacy in patients with chronic illnesses; however, its impact on CKD patients receiving HD has not been thoroughly examined. This research aims to assess the impact of a digital storytelling intervention on boosting self-efficacy in CKD patients undergoing HD. A quasi-experimental design with a non-equivalent control group was employed to examine the intervention's effects. The study involved 40 CKD patients from Bhayangkara Hospital Makassar, selected using purposive sampling. Of these, 27 patients were allocated to the intervention group, and 13 to the control group. The intervention group participated in digital storytelling sessions twice weekly for four weeks, with each session lasting 15-20 minutes. The Chronic Kidney Disease Self-Efficacy (CKD-SE) questionnaire was administered pre- and post-intervention to measure self-efficacy. Data were analyzed using paired t-tests for within-group changes and ANOVA to compare results between the groups. After the digital storytelling intervention, 85.2% of participants in the intervention group showed improvement in self-efficacy, though the change did not reach statistical significance (p = 0.215). Meanwhile, the control group experienced a decrease in self-efficacy over the same period. Despite the encouraging results, the brief duration of the intervention may have limited its full effectiveness. Digital storytelling appears to be a useful method for enhancing self-efficacy in CKD patients undergoing HD. Although the improvements were not statistically significant, the positive trends suggest potential benefits. Future studies should consider extending the duration of the intervention and increasing the sample size to better evaluate its efficacy.